Validity of the Alberta Infants Motor Scale in Norwegian infants aged 6–9 months through comparison with Canadian and Dutch scores - Göthner, Anniken; Riiser, Kirsti; Tveten, Kine Melfald (Frontiers in Pediatrics, 2025)
IntroductionThe Alberta Infant Motor Scale (AIMS) is widely used to assess infant motor development but has shown limited cross-cultural validity in various populations. The distribution of the original AIMS scores has not been cross-culturally validated for Norwegian infants. This study aimed to evaluate the applicability of the Canadian AIMS norm reference for Norwegian infants aged 6–9 months and compare their percentile rankings with the Canadian and Dutch norms.MethodsIn this cross-sectional study, AIMS scores from a sample of 189 Norwegian infants aged 6–9 months were compared to the Canadian and Dutch norms. Total raw scores from the Canadian norms were compared to those of the Norwegian sample, and the percentiles of the Canadian and Dutch sample were compared to tentative Norwegian percentiles.ResultsNorwegian infants aged 6–9 months consistently scored lower on the AIMS than their Canadian counterparts (p < 0.001), with 81% scoring at or below the 50th percentile and 18% falling at or below cut-off indicating possible motor delay. Using the Dutch norms, 20% of the Norwegian sample scored at or below the 50th percentile, while only 1% scored at or below the cut-off. A comparison of the percentile ranks showed that Canadian norms had the highest ranks for all age groups, followed by the Norwegian sample and subsequently the Dutch norms. The observed difference is considered clinically significant.ConclusionNeither Canadian nor Dutch AIMS norms are valid for Norwegian infants due to the Canadian norms being too stringent and the Dutch norms being too lenient. A thorough cross-cultural validation for infants 0–18 months to establish Norwegian-specific AIMS norms is recommended.